Clustering of smoking, alcohol consumption and weight gain in pregnancy: prevalence, care preferences and associated factors - Clare Desmet; Renee Reynolds; Jenna Hollis; Milly Licata; Justine Daly; Emma Doherty; Belinda Tully; Christophe Lecathelinais; John Wiggers; Melanie Kingsland (BMC, 2023)
Abstract Background Smoking, alcohol consumption and weight gain outside recommendations during pregnancy are preventable health risk factors associated with poorer health outcomes for mother and infant. Clustering of these risk factors further increases the risk and severity of outcomes. Limited research has explored the characteristics of pregnant women that are associated with clustering of these risks and women's preferences for receiving support. This paper aimed to determine: (i) the prevalence of clustered preventable risk factors; (ii) associations between maternal characteristics and presence of clustered risk factors; and (iii) women's preferences for receiving care for clustered risk factors. Methods A cross-sectional survey was undertaken with women who had recently given birth in public maternity services in New South Wales, Australia. Descriptive statistics were used to assess prevalence of clustered risk factors and care preferences. Associations between the presence of clustered risk factors and maternal characteristics were assessed using multiple regression analyses. Results Of the 514 women who completed the survey, 52% reported one preventable health risk factor and 10% and 2% reported two or three. For women with two or more risk factors, the most common combination was alcohol consumption and gestational weight gain outside of recommendations (50%, n = 30). One characteristic had an association with the presence of clustered risk factors. Most women (77%, n = 46) with clustered risk factors indicated they wanted support for these health risks. Preferences for support addressing some or all risk factors, and whether the support was sequential or simultaneous, were not associated with particular risk factor combinations. Conclusions Around one in eight women reported clustered preventable risk factors during pregnancy, most of whom would like support to address these risks. There was only one association between maternal characteristics and clustered risk factors. This suggests a need for antenatal care that is women-centred and caters for a diverse profile of clustered risks and varied preferences for care.